Relationship between Education, Knowledge, Attitude, Behavior and Family Support with Antenatal Care (ANC) Visit Frequency among Expectant Mothers in the Ermera District Timor Leste, 2013 - Honoria D.F.P. Carvalho; Nyoman Tigeh Suryadhi; Luh Putu Lila Wulandari (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Regional government recommendations require that 80% of all pregnant mothers visit an antenatal care clinic, however, Ermera District has yet to fulfil this target (34.5%). Low levels of access to antenatal care clinic services impacts negatively on maternal and infant mortality. This study aims to determine the relationship between education, knowledge, attitudes, behaviors and family support with ANC clinic access among pregnat mothers in Ermera District, Timor Leste. Methods: A cross-sectional design was adopted with a sample of 87 pregnant mothers, drawn by the method of multistage cluster random sampling of 9.886 population. The dependent variable was the ANC clinic, while maternal education, knowledge, attitude, behavior and family support were independent variables. Data were collected through self-administered questionnaires, however for the illiterate, researcher assisted completion of the instrument. Data analysis was conducted in stages included univariate, bivariate (chi-squared test) and multivariate (logistic regression) analysis. Results: The results of bivariate analysis indicated there was significant association between knowledge (p=0.002), attitude (p=0.012), behavior (p=0.030), and family support (p=0.015) with the ANC in pregnant women. Multivariate analysis indicated that there was an association between maternal knowledge and ANC visit frequency. Analysis showed that maternal knowledge was the only variable associated with the ANC visits (p=0.046). Conclusion: Only maternal knowledge is associated with the ANC visit among pregnant mothers in Ermera District, Timor Leste